Lobular Breast Cancer: A Review - Wilson, Natalie; Ironside, Alastair; Diana, Anna; Oikonomidou, Olga (Frontiers in Oncology, 2021)
Invasive lobular carcinoma accounts for 5-15% of all invasive breast cancers, with a marked increase in incidence rates over the past two decades. Distinctive biological hallmarks of invasive lobular carcinoma include the loss of cell adhesion molecule E-cadherin leading to cells with a discohesive morphology, proliferating into single-file strands and estrogen receptor positivity. These key molecular features can make diagnosis difficult as invasive lobular carcinoma is challenging to de-tect both physically and with current standard imaging. Treatment of invasive lobular carcinoma strongly favours endocrine therapy due to low chemosensitivity and lower rates of pathological re-sponse as a result. This review will summarise the distinct biological and molecular features of inva-sive lobular carcinoma, focusing on the diagnostic challenges faced and the subsequent surgical and medical management strategies. Prospective therapeutic options will also be explored, highlighting how furthering our understanding of the unique biology of lobular breast carcinoma is essential in guiding and informing the treatment of patients in the future.